2018
DOI: 10.1080/00223891.2018.1423989
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the DSM–5 Alternative Model Personality Disorder Diagnoses in Turkey, Part 1: LEAD Validity and Reliability of the Personality Functioning Ratings

Abstract: This study addresses longitudinal, expert, all data (LEAD) validity and reliability of the personality functioning ratings in Turkey, which are essential in assessing Criterion A for the entire DSM-5 alternative model for personality disorders (AMPD) diagnoses. A total of 120 consenting patients recruited at a university psychiatry clinic were rated by individual clinicians with respect to DSM-III-R and AMPD criteria. Subsequently, a LEAD panel consisting of 3 senior clinicians convened to reach a consensus pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In the AMPD, the assessment of PD severity was originally conceived of as applying the LPFS as an expert rating on a single five-point scale [40]. Other researchers have applied the LPFS in a more differentiated way by separately rating the four domains [41,42], the 12 subdomains [34,[43][44][45][46], or the 60 prototypical descriptions [47••] and aggregating the ratings afterwards. To systematically collect the information that is relevant to make these ratings, several structured clinical interviews have been developed, including the Semi-Structured Interview for Personality Functioning DSM-5 (STiP-5.1) [34], the Clinical Assessment of the Level of Personality Functioning Scale (CALF) [26], and the Structured Clinical Interview for the Level of Personality Functioning Scale (SCID-AMPD Module I) [35].…”
Section: Severitymentioning
confidence: 99%
See 2 more Smart Citations
“…In the AMPD, the assessment of PD severity was originally conceived of as applying the LPFS as an expert rating on a single five-point scale [40]. Other researchers have applied the LPFS in a more differentiated way by separately rating the four domains [41,42], the 12 subdomains [34,[43][44][45][46], or the 60 prototypical descriptions [47••] and aggregating the ratings afterwards. To systematically collect the information that is relevant to make these ratings, several structured clinical interviews have been developed, including the Semi-Structured Interview for Personality Functioning DSM-5 (STiP-5.1) [34], the Clinical Assessment of the Level of Personality Functioning Scale (CALF) [26], and the Structured Clinical Interview for the Level of Personality Functioning Scale (SCID-AMPD Module I) [35].…”
Section: Severitymentioning
confidence: 99%
“…Internal consistency of the LPFS total score has been shown to be acceptable when computed based on ratings of the four domains [40,42] and very high when computed based on ratings of subdomains [34,46,48,135] or individual items [29, 51, 136••]. Moreover, the four domains [27,29,43,46,51,136••] and the 12 subdomains [47••] also showed rather high internal consistency.…”
Section: Internal Consistency and Latent Structurementioning
confidence: 99%
See 1 more Smart Citation
“…14,15 On the other hand, other studies demonstrated the model lends itself well for instruction, such that graduate students and inexperienced raters were able to apply the model with adequate interrater reliability. [16][17][18] An important way to improve clinical utility and ease of use is to develop assessment instruments for assessing the LPFS and pathological personality traits. Since its publication, several instruments for assessing the LPFS have been developed independently by different research groups, including two interview schedules 3,14 and (at least) three self-report questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies included in this systematic review made use of multimethod measurement. Dereboy, Dereboy, & Eskin (2018) The second study included in this systematic review that made use of multimethod measurement, Zimmermann et al (2014), investigated the association between LPFS ratings and various external criterion measures. Two self-report outcome measures (i.e., number of personality disorder diagnoses and presence versus absence of a personality disorder, both derived from the SCID-II) and one secondhand outcome measure (i.e., an expert-rated measure that was used to score a recorded clinical interview 1 ) related to personality functioning were used by Zimmermann et al (2014) to assess the validity of the LPFS.…”
Section: Discussionmentioning
confidence: 99%